Análisis de servicios y productos turísticos de aventura en la Ruta del Rio, cantón Quevedo año 2021 - Rivera Rivera, Yaneth Ysabel (2021)
This research work is oriented to an analysis of the services and adventure tourism products that will be offered in the Ruta del Rio, as an option for the diversification of the tourist offer of the Canton Quevedo, year 2021. The Canton of Quevedo currently has a good development in tourism and public environment. The development of the project intends to achieve an increase in the development of the tourism sector at the cantonal, provincial and regional level that is governed by "good practices", which ensure the growth and maintenance over time of the services and adventure tourism products offered. This will benefit the owners, employees and neighbors of the Ruta del Rio, Canton Quevedo, where the tourist trade takes place. In this way, through the economic viability of tourism organizations in the long term, this should translate equally into economic prosperity of tourism organizations, which is achieved primarily by offering quality jobs for workers of tourism organizations, thus allowing an optimization in the experience and satisfaction of visitors, as it enables a real cultural exchange based on the attention of our society to tourists.